INVESTIGATING HYBRID ELECTROCOAGULATION-FENTON SYSTEM FOR SUSTAINABLE NICKEL REMEDIATION IN WATER RESOURCE - Miguel Ángel López-Ramírez; Olaya Pirene Castellanos Onorio; Mario Díaz-González; Gerardo González Gómez; Ana Concepción Ramos Martínez (Universitas Trisakti, 2025)
Aim: One of the biggest problems of the 21st century is water scarcity and the lack of optimal treatments to solve a need that is increasing due to the contamination of this resource and growing population. The objective of this research is to conduct laboratory-level research on the efficiency of conventional treatments, advanced oxidation processes, and a modified electrocoagulation treatment. Methodology and results: The process known as typical treatment with aluminum sulfate at concentrations of 75, 150, and 225 mg and pH levels of 2, 3, and 4; Fenton reaction at the above concentrations using ferrous sulfate and 0. 22 mL of hydrogen peroxide at the above pH conditions; electrocoagulation with Fenton was performed at a voltage of 17.5 and 19 V, using aluminum electrodes and Fenton reagent conditions similar to the above-mentioned process, except for the medium, where a pH of 8 and 10 is proposed. According to the above experiments, the following results were obtained respectively: Typical treatment with an average removal of 0%, Fenton maximum average removal of 50% at pH 4 and 225 mg of reagent; modified electrocoagulation obtained maximum average removals of 97.6% at pH 8, 19 V, 75 mg of Fenton, and 60 min. Conclusions, Significance, and Impact Study: The addition of Fenton reagent to the electrocoagulation process helps to reduce the reaction time to 30 minutes, according to the literature, making modified electrocoagulation a viable treatment for nickel-contaminated water, in addition to achieving higher removal results than other treatments.